The risks of artificial intelligence on job loss in the field of human resources: Opinions from a sample of university professors specialized in human resource management - Djezzar, Wahiba (The International tax journal, 2025)
This study aims to shed light on the risks of artificial intelligence in causing job loss in the field of human resources. It relies on the opinions of a selected group of academic university professors who specialize in human resource management. The study reflects the real situation faced by human capital as AI applications become more widespread. These developments have led to a reduced need for human input, which in turn creates risks and challenges that affect individuals, society, and the economy. To achieve the study's objectives, 70 questionnaires were analyzed. These resources were distributed to university professors specialized in human. The analysis showed a statistically significant relationship between the use of artificial intelligence and job loss in the human resources field. The participants confirmed this finding and stressed the need for a smooth and well-managed transition to artificial intelligence within institutions. They also emphasized the importance of recognizing the knowledge and capabilities that human resources continue to provide.